Neuro-pharmacological effects of Crinum zeylanicum in mice - Adeniyi Yahaya Tijani; Oluwakanyinsola Adeola Salawu; Good-luck Jaiyeoba; Joseph Akponso Anuka; Isah Marte Hussaini (Mashhad University of Medical Sciences, 2012)
Objectives: The aim of present study was to evaluate some effects of Crinum zeylanicum (C. zeylanicum) on central nervous system. Materials and Methods: C. zeylanicum methanolic bulb extract (250-1000 mg/kg orally), 2 mg chlorpromazine and 4 mg diazepam /kg body weight intraperitoneally respectively were tested in mice using Irwin test, pentobarbitone-induced sleep test, spontaneous motor activity, apomorphine-induced stereotype behaviour, and rota-rod performance. Results: The C. zeylanicum bulb extract significantly and dose-dependently decreased apomorphine-induced hyperactivity in mice (p